2021
DOI: 10.1007/s00775-021-01849-9
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature stable multitalent: highly reactive and versatile copper guanidine complexes in oxygenation reactions

Abstract: Inspired by the efficiency of natural enzymes in organic transformation reactions, the development of synthetic catalysts for oxygenation and oxidation reactions under mild conditions still remains challenging. Tyrosinases serve as archetype when it comes to hydroxylation reactions involving molecular oxygen. We herein present new copper(I) guanidine halide complexes, capable of the activation of molecular oxygen at room temperature. The formation of the reactive bis(µ-oxido) dicopper(III) species and the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 75 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The oxidation of external substrates with bis( μ ‐oxido) copper complexes is well known, ‐ e. g., Herres‐Pawlis and co‐workers described the oxidation of 2‐naphthol to the corresponding ortho quinone [28] . Trials to oxidize this substrate with the copper complexes reported herein only led to the formation of BINOL.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…The oxidation of external substrates with bis( μ ‐oxido) copper complexes is well known, ‐ e. g., Herres‐Pawlis and co‐workers described the oxidation of 2‐naphthol to the corresponding ortho quinone [28] . Trials to oxidize this substrate with the copper complexes reported herein only led to the formation of BINOL.…”
Section: Resultsmentioning
confidence: 81%
“…The oxidation of external substrates with bis(μ-oxido) copper complexes is well known, -e. g., Herres-Pawlis and co-workers described the oxidation of 2-naphthol to the corresponding ortho quinone. [28] Trials to oxidize this substrate with the copper complexes reported herein only led to the formation of BINOL. This was not surprising because the oxidative coupling reaction is already described in the literature using copper(II) amine complexes.…”
Section: Oxidation Of External Substratesmentioning
confidence: 84%
“…The so-called peroxido complex is mimicking the catalytically active Cu 2 O 2 center of tyrosinase [49]. Since then several peroxido and oxido catalysts complexes were published converting various simple phenolic substrates [50][51][52][53][54]. Those two Cu 2 O 2 species are structural isomers existing in an equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, their reaction velocity and reaction properties are totally different. The oxido complex generated by [Cu(TMGbenza)I] is stable at room temperature but the formation takes very long (2 h), whereas the one of [Cu(TMGbenza)]OTf is only formed at low temperatures but within 3 min [53,54]. As a result, even small modifications on the molecule structure, as the exchange of the corresponding anion, can cause completely different reaction velocities.…”
Section: Introductionmentioning
confidence: 99%
“…19,22,28 We are focusing on guanidine ligands due to their excellent N donor properties and a large versatility in ligand design. 29,30 Besides exhibiting good activity in ATRP, [31][32][33][34][35][36][37][38][39][40][41] guanidine based catalysts can be used for oxygen activation, 42 ring-opening polymerisation, 43 and photochemistry 44 and further as model complexes for the entatic state of electron transfer proteins. 45 Our previous studies on guanidine quinolinyl (GUAqu) catalysts in ATRP show that the solubility, electronic properties, and therefore the catalytic activity can be increased by the substitution of the quinolinyl backbone.…”
Section: Introductionmentioning
confidence: 99%